Green Extract from Pre-Harvest Tobacco Waste as a Non-Conventional Source of Anti-Aging Ingredients for Cosmetic Applications - Mariana Leal; María A. Moreno; María E. Orqueda; Mario Simirgiotis; María I. Isla; Iris C. Zampini (Plants, 2025)
The cigarette production from Nicotiana tabacum generates significant amounts of waste, with an estimated 68.31 million tons of pre- and post-harvest waste discarded annually. The pre-harvest waste includes the upper parts of the plant, inflorescences, and bracts, which are removed to help the growth of the lower leaves. This study explores the potential of apical leaves from Nicotiana tabacum var. Virginia, discarded during the budding stage (pre-harvest waste). The leaves were extracted using environmentally friendly solvents (green solvents), including distilled water (DW) and two natural deep eutectic solvents (NaDESs), one consisting of simple sugars, fructose, glucose, and sucrose (FGS) and the other consisting of choline chloride and urea (CU). The anti-inflammatory and anti-aging potential of these green extracts was assessed by the inhibition of key enzymes related to skin aging. The xanthine oxidase and lipoxygenase activities were mostly inhibited by CU extracts with IC50 values of 63.50 and 8.0 μg GAE/mL, respectively. The FGS extract exhibited the greatest hyaluronidase inhibition (49.20%), followed by the CU extract (33.20%) and the DW extract (20.80%). Regarding elastase and collagenase inhibition, the CU extract exhibited the highest elastase inhibition, while all extracts inhibited collagenase activity, with values exceeding 65%. Each extract had a distinct chemical profile determined by LC-ESI-QTOF-MS/MS and spectrophotometric methods, with several shared compounds present in different proportions. CU extract is characterized by high concentrations of rutin, nicotiflorin, and azelaic acid, while FGS and DW extracts share major compounds such as quinic acid, fructosyl pyroglutamate, malic acid, and gluconic acid. Ames test and Caenorhabditis elegans assay demonstrated that at the concentrations at which the green tobacco extracts exhibit biological activities, they did not show toxicity. The results support the potential of N. tabacum extracts obtained with NaDESs as antiaging and suggest their promising applications in the cosmetic and cosmeceutical industries.